STRATEGI TIM REDAKSI PROGRAM LENSA MANAKARRA DALAM MENINGKATKAN KUALITAS PEMBERITAAN DI PT MANAKARRA TV SULAWESI BARAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses the strategy of the Manakarra Lens Program Editor Team at PT. Manakarra TV West Sulawesi in Improving the Quality of Coverage. The research objectives (1) To determine the strategy and presentation of the Manakarra TV editorial team on the Manakarra Lens program in improving the quality of its news. (2) To trace the production process of the Manakarra Lens program in improving the quality of news. This type of research is qualitative research. This type of research is descriptive research. By using data collection methods, namely, observation, interviews or interviews and documentation. The data sources in this study were obtained from direct interviews with several informants at the research location, including the editor in chief, presenter, editor, cameraman and journalist Lens Manakarra. Data processing and analysis techniques are through data collection, data reduction process, data presentation and conclusion drawing. The results showed that the first Manakarra Lens news production process was planning, field coverage, audio-visual editing, the production stage by the operator team and post-production evaluating the broadcast. The strategy of the Manakarra Lens program editorial team in improving the quality of the news includes (1) presenting news editors that are concise, precise and easy to understand, (2) presenting program programs about West Sulawesi Province that are factual, actual and balanced. The implication of this research is that PT. Manakarra TV should add more employees, especially in the area of coverage or a team of journalists and recruitment of competent human resources, updating equipment, improving the quality of program packaging and paying attention to errors in the display of programs offered to the public, and presenting more actual news.